2013
DOI: 10.1123/jab.29.4.371
|View full text |Cite
|
Sign up to set email alerts
|

Humeral Head Translation After a Suprascapular Nerve Block

Abstract: Subacromial impingement syndrome is the most common shoulder disorder. Abnormal superior translation of the humeral head is believed to be a major cause of this pathology. The first purpose of the study was to examine the effects of suprascapular nerve block on superior translation of the humeral head and scapular upward rotation during dynamic shoulder elevation. The secondary purpose was to assess muscle activation patterns during these motions. Twenty healthy subjects participated in the study. Using fluoro… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1

Citation Types

2
5
0

Year Published

2013
2013
2021
2021

Publication Types

Select...
8
1

Relationship

0
9

Authors

Journals

citations
Cited by 20 publications
(7 citation statements)
references
References 41 publications
2
5
0
Order By: Relevance
“…An advantage of MR scanning for the assessment of the humeral translation in this study is the non-invasive nature of the instrument and no need to prepare for the analysis. In fluoroscopic studies (Matsuki et al 2012 ; San Juan et al 2013 ), a biplane radiographic study (Bey et al 2008 ) and a motion capture study (Dal Maso et al 2015 ), the number of subjects was restricted due to radiation exposure (Bey et al 2008 ; Matsuki et al 2012 ; San Juan et al 2013 ) or to markers mounted into bone (Dal Maso et al 2014 , 2015 ). A three-dimensional (3D) MRI study attempted to scan continuous shoulder elevation (Pierrart et al 2014 ).…”
Section: Discussionmentioning
confidence: 99%
“…An advantage of MR scanning for the assessment of the humeral translation in this study is the non-invasive nature of the instrument and no need to prepare for the analysis. In fluoroscopic studies (Matsuki et al 2012 ; San Juan et al 2013 ), a biplane radiographic study (Bey et al 2008 ) and a motion capture study (Dal Maso et al 2015 ), the number of subjects was restricted due to radiation exposure (Bey et al 2008 ; Matsuki et al 2012 ; San Juan et al 2013 ) or to markers mounted into bone (Dal Maso et al 2014 , 2015 ). A three-dimensional (3D) MRI study attempted to scan continuous shoulder elevation (Pierrart et al 2014 ).…”
Section: Discussionmentioning
confidence: 99%
“…Furthermore, de Witte et al [21] suggested that decreased abduction torque by the supraspinatus and infraspinatus in the presence of a tear may be compensated for by increased deltoid activity, which, in turn may be associated with increased superior glenohumeral translation. Greater relative add uctor activity during isometric abd uction (lower AR) could be a compensatory strategy by the adductors to reduce the upwards, cranial humeral head translation evident with loss of rotator cuff function [20,38]. Cadaveric studies [39,40] suggest that latissimus dorsi, teres major, and pectoralis major are strong depressors of the glenohumeral head, along with the rotator cuff and long head of biceps brachii.…”
Section: Discussionmentioning
confidence: 99%
“…This result is in accordance with Sciascia et al [ 32 ] while subjects performed the PUP exercise. During humeral elevation in the scapular plane, infraspinatus activity has been reported to be between 10% - 25% MVC [ 29 , 38 ]. Conversely, it has been shown that sidelying external rotation exercise and prone external rotation can elicit a great amount of EMG activity equal to 62% and 63% MVIC, respectively [ 32 , 39 ].…”
Section: Discussionmentioning
confidence: 99%